Le chemin du pouvoir - Kautsky, Karl; Fay, Victor; Adler, Victor; Bebel, August; Dietz, J.H.W.; Haase, Hugo; Herzfeld, Joseph; Zetkin, Clara (Paris : Anthropos, 1969)
Fonds Perrone
Frans
Monografie
Keywords: sociaaldemocratie